African belief and knowledge systems : a critical perspective - Mawere, Munyaradzi (Langaa Research & Pub. CIG, 2011)
The debate on the existence of African philosophy has taken central stage in academic circles, and academics and researchers have tussled with various aspects of this subject. This book notes that the debate on the existence of African philosophy is no longer necessary. Instead, it urges scholars to demonstrate the different philosophical genres embedded in African philosophy. As such, the book explores African metaphysical epistemology with the hope to redirect the debate on African philosophy. It articulates and systematizes metaphysical and epistemological issues in general and in particular on Africa. The book aptly shows how these issues intersect with the philosophy of life, traditional beliefs, knowledge systems and practices of ordinary Africans and the challenges they raise for scholarship in and on philosophy with relevance to Africa.